Determining a priori estimate of error in the thermal protection of gas generator in a hydrogen storage and supply system - Abramov, Yuriy; Basmanov, Oleksii; Krivtsova, Valentina; Mikhayluk, Andriy; Bogatov, Oleg; Sobyna, Vitalii; Neklonskyі, Ihor; Chernysh, Roman (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates a gas generator for a hydrogen storage and supply system with a heat-shielding coating. The subject is the properties of the heat-shielding coating of the gas generator for a hydrogen storage and supply system under fire conditions. The properties of such a heat-shielding coating are taken into account by the thermal protection error of the thermodynamic system, which includes the heat-shielding coating and the gas generator wall. To describe the dynamic properties of the thermodynamic system in the frequency domain, amplitude-phase frequency characteristics and their components – amplitude-phase and phase-frequency characteristics – are used. The frequency characteristics of the thermodynamic system have been mathematically described in general form. It is shown that for the characteristic values of parameters for the thermodynamic system, its properties are fully reflected using frequency characteristics in the frequency range (0÷1.0) s-1 at a bandwidth of 0.02 s-1. The thermal effect of fire on the thermal state of the cavity of the gas generator of the hydrogen storage and supply system is taken into account using exponential-type correlation functions. Thermal interference is "white noise". Under these conditions and using the amplitude-frequency characteristics of the thermodynamic system, mathematical models of the components of the error of the thermal protection of the gas generator were built in general form. As an indicator characterizing the error of the thermal protection of the gas generator, its root mean square value was used. It is shown that for real fire conditions and operation of hydrogen storage and supply systems, the root mean square error of the thermal protection of the gas generator is 5.14°C. In practice, the existence of such an error estimate opens up the possibility for improving the reliability in determining the thermal protection for a gas generator.